Relationship between the Village Government and the Village Consultative Body in the Formulation of the APBdes in Sidoraharjo Village, Kedamean District, Gresik Regency - Suwoto Suwoto; Ika Devy Pramudiana; Dian Ferriswara; Sri Kamariyah (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study aims to describe and analyze: the relationship between the village government and the village consultative body (BPD) in the formulation of the APBDes and the obstacles faced by the village government and the village consultative body in the formulation of the APBDes in the village. The data analysis technique in the study uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study showed. The relationship between the Village Government and BPD in the formulation of the Village Revenue and Expenditure Budget in Sidoraharjo Village, Kedamean District, Gresik Regency is a partnership. Each institution carries out its roles and functions in accordance with Gresik Regent Regulation Number 25 of 2024, Law Number 22 of 1999 and Law Number 23 of 2014. This relationship between the implementation of the legislative function of formulating the village budget and expenditure by the BPD and the Sidoraharjo Village Government has been carried out and in accordance with the Laws and Regulations and the correct stages. The authority of the BPD and the Village Government is to discuss the draft budget and village expenditure in accordance with the stages of the stages, namely the initiation stage, the socio-political stage, and the juridical stage. The implementation of coordination in the formulation of the village budget and expenditure by the BPD and the Sidoraharjo Village Government has been carried out and in accordance with the Laws and Regulations and the correct stages. The Village Government and BPD have carried out their respective wars through the preparation stage, making budget plans and ratification carried out together. The Village Consultative Body (BPD) has carried out its supervisory function by supervising all actions taken by the Village Executive on the implementation of the village budget and expenditure Obstacles faced by the Village Government and BPD in the process of formulating the village revenue and expenditure budget include: Internal obstacles are human resources (human resources) that are not qualified in the economic field External obstacles are the lack of technical guidance from the Regional Government, especially in the field of legislation.